SMEs Performance and Halal Food Supply Chain - Ayuk Setiyawan; Muzakar Isa; M. Farid Wajdi (Universitas Muhammadiyah Ponorogo, 2023)
The food and beverage business has a strategic role in the economy and food security, where 90% of national food products are provided by SMEs. SMEs also control 99.9% of the industrial market, absorb 97% of the national workforce and contribute 60% to GDP. On the other hand, food and beverage SMEs have the lowest resistance to the COVID-19 pandemic, so efforts need to be made to strengthen organizational resilience to the uncertainty of the business environment. This study aims to describe the food and beverage business supply chain, analyze the level of business efficiency and analyze the key variables of the performance of food and beverage SMEs in Surakarta City after the covid-19 pandemic. This research uses supply chain analysis, efficiency analysis and structural analysis. Supply chain analysis uses descriptive qualitative analysis. Efficiency analysis uses a non-parametric approach whose defeat uses DEAP. Analysis of determining the key variables of SME performance using structural analysis. The study used 20 variables to be processed into key variables for the performance of SMEs. The research involves academia, business, government, and the community (ABGC) in FGDs to obtain a comprehensive study. Data analysis using structural analysis using MICMAC.The results of the study explain that the performance of food and beverage SMEs was influenced by the product supply chain, there are still many food and beverage businesses that have not yet reached the level of efficiency, either in resource allocation or in achieving output. The results also explain 5 key variables out of 20 variables that are used to determine the main variables that have a high influence in supporting business performance, namely achievement-oriented, effective marketing, optimism, market understanding, and risk management.